Profound Methyl Effects in Drug Discovery and a Call for New CH Methylation Reactions. Issue 47 (22nd October 2013) - Schönherr, Heike; Cernak, Tim
Abstract The methyl group is one of the most commonly occurring carbon fragments in small‐molecule drugs. This simplest alkyl fragment appears in more than 67 % of the top‐selling drugs of 2011 and can modulate both the biological and physical properties of a molecule. This Review focuses on so‐called magic methyl effects on binding potency, where the seemingly mundane change of CH to CMe improves the IC50 value of a drug candidate more than 100‐fold. This discussion is followed by a survey of recent advances in synthetic chemistry that allow the direct methylation of C(sp2)H and C(sp3)H bonds. It is our hope that the relevance of the meager methyl group to drug discovery as presented herein will inspire reports on new CH methylation reactions.